VULNERABILITY TO POVERTY IN MALAYSIA: WHAT LONGITUDINAL DATA CAN TELL US? - Senadjki, Abdelhak; Sulaiman, Jamalludin; Mohd, Saidatulakmal (ASIAN JOURNAL FOR POVERTY STUDIES (AJPS), 2015)
In developing countries, many household are exposed to high risk, uncertainties and crises, which not only causes of poverty,Â but also a path to micro-economic downturn. Studies have shown that households who have the fewest instruments toÂ deal with these risks are considered poor. In some cases, they are seen as the most vulnerable. In Malaysia, both povertyand a wide variety of risks are widespread among household member, especially in the rural areas. The present researchÂ aims to examine rural householdsâ vulnerability to poverty using longitudinal data set of three waves. The present studyÂ developed and designed (an alternative to panel data) modules in cross-sectional surveys with recall questions that can beused to tract a householdsâ history and its evolution along various welfare dimensions. The study aims, in general, toÂ analyse the link between exposure to risks and vulnerability to poverty of rural households in Kelantan and Terengganu.Â Data was collected from a three-round panel survey undertaken at 6 month interval to allow measurement of seasonalÂ variation in behaviour and outcome and to balance both cross-sectional and time series requirements of panel data. 460Â respondents were interviewed in the first round, but only 301 questionnaires in the last round were valid for dataanalysis. The findings illustrated that fighting future poverty is not only to incorporate monetary measure but also nonÂ -monetary measure need to be merged. The lack of access to assets and resources and the exposure to threats haveÂ made the process of recovering from poverty unsuccessful. Assets are regarded as the core element of vulnerabilityÂ reduction. Both covariate and idiosyncratic risks are central causes behind a household future vulnerability. TheÂ effect of these threats is determined by its nature and level of severity, as well as by the type of strategies to respond tothe threats.